(untitled) (Research, Society and Development, 2022)
Objective: to identify the main therapeutic interventions in the management of patients with non-Hodgkin’s lymphoma. Material and methods: In order to answer the research question “What are the main therapeutic interventions in the management of patients with non-Hodgkin’s lymphoma?”, a systematic review of the literature was chosen. The research will be carried out through a search, based on a search strategy, in the Medical Publisher (PUBMED) and Science Direct databases, with the objective of selecting articles related to therapeutic interventions in the management of patients with non-invasive lymphoma. -Hodgkin. Results: the association of rituximab with chemotherapy and with lenalidomide may allow prolonged responses in some patients and represents an effective therapeutic option. The high-dose chemotherapy strategy with autologous stem cell transplantation has been shown to be viable and highly effective in patients with primary central nervous system lymphoma, providing a better prognosis for patients. Final considerations: it is possible to state that the therapy of choice initially for the management of patients with non-Hodgkin’s lymphoma still continues to be the association of rituximab with chemotherapy in the R-CHOP regimen, with the possibility of still being associated with lenalidomide, allowing answers prolonged in some patients and representing an effective therapeutic option. Maintenance therapy with rituximab has been shown to improve progression-free survival in patients with follicular lymphoma, improving survival rates and the duration of disease remission. Combined modality therapy (chemotherapy + immunotherapy) may have better outcomes and prognosis for patients with diffuse large B-cell lymphoma.